ASUHAN KEBIDANAN TERHADAP IBU HAMIL DENGAN KEJADIAN PREEKLAMPSIA - Ulpawati; susanti; Miftahul Jannah (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Preeclampsia is a syndrome characterized by increased blood pressure, proteinuria, and fluid retention that appears in the second trimester of pregnancy or more than 20 weeks and will recover in the postnatal period. The purpose of this study was to carry out midwifery care for pregnant women with mild preeclampsia. The research method is a case study with Varney's 7-step Antenatal Midwifery Care Management and documentation in SOAP at BPM Suratmi, Batam City. The case study results were conducted on Mrs "S" with mild preeclampsia, there were no obstacles in handling this case study. The treatment that was carried out on Mrs. "S" was by recommending that she routinely check her pregnancy to see the condition of the mother and the condition of the fetus and give anti-hypertensive drugs, namely the drug Nifedipine 10 mg. The conclusions from the case studies include documentation in the form of SOAP which is used for the process of solving midwifery problems, monitoring studies and data analysis have been carried out on Mrs. "S" with Mild Preeclampsia at BPM Suratmi, Batam city for four weeks and home visits four times, the results obtained are blood pressure has decreased from 145/90 to 120/80 mmHg, Negative proteinuria and reduced swelling of the legs, a study has been carried out documenting all findings and actions that have been carried out on Mrs. "S" with the result that no discrepancy between theory and case studies was found.